Models for the estimation of diffuse solar radiation for typical cities in Turkey. (15th March 2015) - Bakirci, Kadir
Abstract: In solar energy applications, diffuse solar radiation component is required. Solar radiation data particularly in terms of diffuse component are not readily affordable, because of high price of measurements as well as difficulties in their maintenance and calibration. In this study, new empirical models for predicting the monthly mean diffuse solar radiation on a horizontal surface for typical cities in Turkey are established. Therefore, fifteen empirical models from studies in the literature are used. Also, eighteen diffuse solar radiation models are developed using long term sunshine duration and global solar radiation data. The accuracy of the developed models is evaluated in terms of different statistical indicators. It is found that the best performance is achieved for the third-order polynomial model based on sunshine duration and clearness index. Highlights: Diffuse radiation is given as a function of clearness index and sunshine fraction. The diffuse radiation is an important parameter in solar energy applications. The diffuse radiation measurement is for limited periods and it is very rare. The new models can be used to estimate monthly average diffuse solar radiation. The accuracy of the models is evaluated on the basis of statistical indicators.